PENGARUH HARGA,DISTRIBUSI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI PT. SMARTFREN TBK PALEMBANG - Herman Efrizal (JURNAL KOMPETITIF, 2016)
This research studies the correlation among price, distribution,promotion and buy decision at Govermance Smartfren TBK Palembang.This research was done during 6 (six)month included design,executing and report the result.The research of this case study aims to know the correlation among price, distribution ,promotion and buy decision at Govermance Smartfren TBK Palembang either through parsial and also together.The population in this research are the officer at Govermance Smartfren TBK Palembang,totally 83 respondent. Keywords: price,distribution,promotion and buy decision